Parasitinsekten der Insektengallen Europas. - Fulmek, Leopold (Contributions to Entomology = Beiträge zur Entomologie, 1968)
Nearly 2200 different species of insect parasites were registered in about 600 insect galls. The statistics of these parasites and the tabulation of the frequency of data provided material for a detailed discussion of the relations between the six orders of hosts (C, D, H, L, R, T) and their parasites. It appears that the parasite-hostrelations not only facilitate the nomenclature of the different parasites but should also be included in the keys to supplement the taxonomie characteristics (on a natural basis, as opposed to a purely human fiction). This is justified by the fact that species, e.g. of ichneumon flies, which were first regarded as separate, turned out to be males and females of the same species, as control breedings in some cases have proved.